2010
DOI: 10.1590/s1678-77572010000500017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the simulated periodontal ligament on cast post-and-core removal using an ultrasonic device

Abstract: ObjectiveThe aim of this study was to evaluate the effect of simulated periodontal ligament (SPDL) on custom cast dowel and core removal by ultrasonic vibration.Material and MethodsThirty-two human maxillary canines were included in resin cylinders with or without SPDL made from polyether impression material. In order to allow tensile testing, the roots included in resin cylinders with SPDL were fixed to cylinders with two stainless steel wires. Post-holes were prepared by standardizing the length at 8 mm and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
2
4
0
1
Order By: Relevance
“…Comparison of the results of the ultrasound groups and the control group (without ultrasonic vibration) in the present study confirmed the effectiveness of the Enac in reducing the load necessary to remove intraradicular cast posts, as reported elsewhere (10,14,16). Several studies have reported that the type of luting agent can have an influence on the ultrasonic efficiency for post removal (12,13).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Comparison of the results of the ultrasound groups and the control group (without ultrasonic vibration) in the present study confirmed the effectiveness of the Enac in reducing the load necessary to remove intraradicular cast posts, as reported elsewhere (10,14,16). Several studies have reported that the type of luting agent can have an influence on the ultrasonic efficiency for post removal (12,13).…”
Section: Discussionsupporting
confidence: 90%
“…Usually, the roots of extracted teeth are embedded in resin cylinders in order to facilitate handling and test application. In this step, the simulation of periodontal ligament (PDL) is more consistent with the clinical reality (15,16). In the present study, this procedure was not performed, which could represent a methodological limitation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, various studies that assess bond strength between root canal posts and dentin after mechanical fatigue do not simulate periodontal ligament 3 , 8 . Similarly, most studies fail to simulate the periodontal ligament in fracture resistance tests 5 , 18 , although a few studies simulate the periodontal ligament using polyether 11 , 13 and polivynilsiloxane based elastomers 7 , 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Bu nedenlerle, yapılan laboratuvar çalışmalarının klinik ortamını simule edebilmesi için periodontal ligament ve kemik dokusunun laboratuvar çalışmalarda taklit edilmesi gereklidir (2). Periodontal ligament oluşturulan çalışmaların bazılarında materyal olarak polieter (4,5) ve polivinilsilikon bazlı elastomerler (1,6) tercih edilmiştir. Restoratif materyaller birçok avantaja sahip olmasına rağmen, pulpa dokusu bulunmayan dişlerde vertikal kök kırıkları halen bilinen önemli problemlerdendir (7,8).…”
Section: Introductionunclassified